CRITICAL REVIEW OF TASKS IN ENGLISH TEXTBOOK “WHEN ENGLISH RINGS A BELL” - Aryani Aryani; Ikhsanudin Ikhsanudin; Regina Regina (Fakultas Keguruan dan Ilmu Pendidikan Universitas Tanjungpura, 2018)
Textbook plays an important role in English language teaching. Therefore evaluating a textbook is needed. It is interesting to analyse the newest textbook provided by the government due to it is used as a compulsory textbook. This study used a framework proposed by Littlejohn (2011). It is a subjective analysis level. The study focused on three key aspects of tasks; (1) what is the learners expected to do; (2) who are the learners to work with; and (3) what is the content focus for. This was a qualitative content analysis study. The data of the research is